Pengaruh Pembatasan Sosial dan Variabel Ekonomi Terhadap Prevalensi Pandemi Covid-19 di Provinsi Jawa Barat - Aperdanaste, Jordi; Hasanah, Alfiah; Siregar, Adiatma Y. M. (Jurnal Ekonomi Kesehatan Indonesia, 2021)
There are numerous factors that might affect social restrictions regulation on the reduction of the number of Covid-19 cases in 27 cities and districts in West Java Province. This study aims to identify the effect of social restrictions and economic variables on Covid-19 pandemic in West Java Province. The investigation uses several data sourced from the Covid-19 Information & Coordination Center of West Java Province, and the Central Bureau of Statistics in West Java Province. The dependent variable in this study is the average increase in daily Covid-19 cases. Meanwhile, the independent variable in this study are dummy of social restrictions, population density, per capita GRDP, education level, mobility level, unemployment rate, number of health workers, percentage of the poor population, and life expectancy. All the information gathered in the period between March 2, 2020 and March 2, 2021, which consists of 17 periods based on the Decree of the Governor of West Java. A panel data analysis with the Feasible Generalized Least Square (FGLS) approach is applied using Stata MP-64 software. The results show that social restrictions, population density, unemployment rate, and the number of health workers have a positive and significant effect against the reduction of the Covid-19 cases in West Java Province. Per capita GRDP shows a positive effect against the reduction of the Covid-19 cases, however it is not significant. Level of education, level of mobility, percentage of the poor population, and life expectancy have a negative and significant effect against the reduction of the Covid-19 cases in West Java Province. Therefore, social restrictions are the right policies to reduce the Covid-19 pandemic in West Java Province.